Long bone histology of Chersina angulata : Interelement variation and life history data. (1st November 2019) - Bhat, Mohd Shafi; Chinsamy, Anusuya; Parkington, John
Abstract: The current study deduced the growth pattern and lifestyle habits of Chersina angulata based on bone histology and cross‐sectional geometry of limb bones. Femora, humeri, and tibiae of seven different‐sized individuals representing different ontogenetic stages were assessed to determine the interelement and intraskeletal histological variation within and among the tortoises. The bone histology of adult propodials consists of a highly vascularized, uninterrupted fibrolamellar bone tissue with a woven texture in the perimedullary and midcortical regions suggesting overall fast early growth. However, later in ontogeny, growth was slow and even ceased periodically as suggested by slowly formed parallel‐fibered bone tissue and several growth marks in the pericortical region. In juvenile individuals, fibrolamellar bone tissue is restricted to the perimedullary regions of propodials as remnants of bone formed during the earliest stages of ontogeny. The epipodials are characterized by having parallel‐fibered bone tissue present in their cortices; however, periodic arrests in growth are recorded at various times. Remnants of fibrolamellar bone tissue formed during early ontogeny occur in the epipodials of only a few individuals. Interelement variation is evident, in terms of variation in the orientation of vascular canals between individuals and within the same diaphyseal cross‐sections. Different elements show varying cross‐sectional geometry, which appear to be correlated with the fossorial behavior of the species. Our results show that of all the long bones, the tibia is least remodeled during ontogeny and it is therefore the best element for skeletochronology. Abstract : A, Angulate tortoise C. angulata from Springbox, Northern Cape, South Africa. B, humerus; D, femur; F, tibia of the largest individual. The dotted lines indicate the histological section planes. C, humerus; E, femur; G, tibia; transverse sections under cross‐polarized light with lambda compensator. Abbreviations: cccb, compacted coarse cancellous bone; cn.cr, cnemical crest; dp, diaphysis; epi, epicondyle; fhd, femoral head, flb, fibrolameller bone; gt, greater trochanter; hhd, humeral head, int. g, intertubercular groove; lb, lameller bone; ms, muscle scar; ne, neck; pfb, parallel‐fibered bone; pop, popliteal fossa; po, primary osteon; prl, peristeal resorption line; rad.c, radial canals; re, resorption cavity; tr. f, trochanteric fossa; so, secondary osteon; wb, woven bone.